PARTISIPASI PEMUDA DALAM PEMBANGUNAN GAMPONG GENUREN KECAMATAN BINTANG, KABUPATEN ACEH TENGAH - Mikasih, Yara; Fitrianti, Fitrianti; Juaris, Juaris (Politeknik STIA LAN Makassar, 2024)
The role of youth is very important in village development, but in reality in the field the role of youth is not as expected, many youth do not care about the development and development of their region because they are too busy with their own activities, making the level of youth participation in village development very minimal. This research aims to find out the level of youth participation in the development of Gampong Genuren and the obstacles. The research method used in this research is qualitative research with a descriptive approach. The data collection methods used in this research include observation, interviews and documentation. The data analysis techniques used in this research are data presentation, data reduction and conclusion drawing. The results of this research show that the level of youth participation in development in Gampong Genuren is still very low, this can be seen from the lack of youth participation in the development decision-making process, the lack of youth participation during development implementation and the lack of youth supervision in village development. The obstacles faced by the youth of Gampong Genuren in village development are due to the lack of communication between village officials and the youth in Musrenbang and the implementation of development activities in Gampong Genuren as well as time constraints on the part of the youth, resulting in minimal youth participation in the development of Gampong Genuren.